Effect of salinity on Seed Germination and Growth of Tomato Seedlings (Lycopersicon esculentum) - F. Abbas, Karima (University of Thi-Qar Journal of Science, 2010)
This study was conducted in a private orchard during growing season 2009 toinvestigate the effects of NaCl application on growth of Tomato (Lycopersiconesculentum). The Saline water used was prepared in Six concentrations namely (1000, 2000, 3000 ,4000 and 5000 ppm) .This study was evaluated in Two steps, seed germination and plant growth. The result showed that salinity caused a delay in seed germination and reduce the number of germinated seeds .At higher NaCl concentration(5000 ppm) , No seed germination was observed. Chlorophyll content & leaf area decreased with increasing salinity. The plant height decreased with increasing salinity. plant fresh and dry shoot and root weights were decreased with increasing salinity. Increasing salinity levels in the water significantly decreased the content of N,K in leaves, and non decreased of P, and increased the content of Na .